Requirement Engineering Aplikasi E-Rapor SMK Negeri 3 Ambon Dengan Pemanfaatan Teknologi RESTful API - Hetharion, Sthania; Bangkalang, Dwi Hosanna (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
SMK Negeri 3 Ambon manages grades using the Implementation of the Independent Curriculum (IKM) assessment format in Microsoft Excel files. However, managing student grades takes a long time to be processed into report card grades. Therefore, an integrated e-report application is needed to help the school manage student grades more efficiently and effectively. The e-report application will be designed as a website using the requirement engineering method by Loucopoulos and Kanakostas, which follows an iterative requirement engineering process model. This system is designed utilizing RESTful API technology to avoid data redundancy, speed up data exchange, and integrate with other systems in use, such as the Advanced Message Queuing Protocol (AMQP). Usability testing was conducted using the System Usability Scale (SUS) to validate the system design. The results obtained from the testing phase showed a score of 74.26%, which indicates that the system is good and acceptable to users.